Analysis on brittleness characteristics of tight oil siltstones. Issue 1 (1st December 2018) - Tan, Wenhui; Ba, Jing; Zhao, Haibo; Fang, Gang; Qian, Wei; Chen, Hao; Yu, Ting; Wu, Chunfang
Abstract : We obtain the basic parameters of the rocks of Qingshankou formation by performing the rock uniaxial and triaxial compression mechanics experiments. Different brittleness indexes are computed and we select the best brittleness index of B2 (E/u, Young's modulus / Poisson's ratio) to evaluate rock brittleness characteristics. The coefficient of brittle stress drop is introduced to evaluate rock brittleness characteristics which coincide with the selected brittleness index. The relationships between brittleness indexes and rock parameters such as elastic parameters, mineral components and reservoir physical properties (porosity, and density) are analyzed. Results show that E and u are the good indicators of rock brittleness, while shale content has no obviously influence on the elastic parameters. Quartz and carbonate minerals are considered as brittle components for evaluating rock brittleness. There is a good correlation between the brittleness index B2 and reservoir porosity, which is important for analyzing rock brittleness characteristics in the study area.